REVITALISASI NILAI KEHIDUPAN FATIMAH AZ-ZAHRA UNTUK PENDIDIKAN ISLAM MODERN DALAM KITAB ‘IQDUL LUL FI SIROTIL BATUL - Ervina; Salamah (IAI DARUL ULUM KANDANGAN, 2025)
This study aims to analyze the ideal values of women's education found in the book ‘Iqdul Lul fi Sirotil Batul by Habib Muhammad bin Hasan bin ‘Alawi al-Ḥaddad, which portrays Fatimah Az-Zahra, the daughter of the Prophet Muhammad Saw., as the ideal female figure in Islam. The main focus of this research is to present Fatimah Az-Zahra as a woman with spiritual, moral, and intellectual excellence. This study uses a qualitative approach by combining hermeneutics and content analysis as a dual approach in examining the book ‘Iqdul Lul fi Sirotil Batul by Habib Muhammad bin Hasan bin ‘Alawi al-Ḥaddad. The findings indicate that the book ‘Iqdul Lul fi Sirotil Batul not only represents the historical narrative of the life of Sayyidah Fatimah Az-Zahra, but also contains a well-constructed and systematic educational framework for shaping the character of Muslim women. Through hermeneutic analysis and content analysis, the educational values contained in this book can be synthesized into four main categories, spiritual values, moral-ethical values, intellectual values, and social-family values.